Smartphone Selection Recommendation System - Sari, Lya Rosita; Wulanningrum, Resty; Swanjaya, Daniel (FAKULTAS TEKNIK UNIVERSITAS ISLAM KADIRI, 2022)
Smartphone is a telecommunications tool that has the same capabilities as conventional telephones, where smartphones are much more practical and easy to carry anywhere. The brands smartphone offered have many models and specifications such as ram, rom, camera, processor and others. To make it easier for users to choose the type of smartphone, it takes a smartphone selection recommendation system to assist users in making a decision. In this study resulted in a smartphone selection recommendation system application that is designed to assist users in making decisions in choosing a smartphone. This system is designed with reference to the calculation results of the Simple Additive Weighting (SAW) method by considering several criteria used to search smartphones. From the results of calculations using the SAW method, the preference values ​​of V1 to V3 are determined where according to alternative data, V1 for alternative A1 with a value of 0.76, V2 for alternative A2 with a value of 0.77, and V3 for alternative A3 with a value of 0.85. So that the largest ranking value is obtained, namely V3 with a value of 0.85. So alternative V3 is the alternative that was chosen as the best alternative.